Current Steering Using Multiple Independent Current Control Deep Brain Stimulation Technology Results in Distinct Neurophysiological Responses in Parkinson’s Disease Patients - Peeters, Jana; Boogers, Alexandra; Van Bogaert, Tine; Gransier, Robin; Wouters, Jan; Nuttin, Bart; Mc Laughlin, Myles (Frontiers in Human Neuroscience, 2022)
Background: Deep brain stimulation (DBS) is an effective neuromodulation therapy to treat people with medication-refractory Parkinson’s disease (PD). However, the neural networks affected by DBS are not yet fully understood. Recent studies show that stimulating on different DBS-contacts using a single current source results in distinct EEG-based evoked potentials (EPs), with a peak at 3ms (P3) associated with dorsolateral subthalamic nucleus stimulation and a peak at 10ms associated with substantia nigra stimulation. Multiple independent current control (MICC) technology allows the center of the electric field to be moved in between two adjacent DBS-contacts, offering a potential advantage in spatial precision. Objective: Determine if MICC precision targeting results in distinct neurophysiological responses recorded via EEG. Materials & Methods: We recorded cortical EPs in five hemispheres (four PD patients) using EEG whilst employing MICC to move the electric field from the most dorsal DBS-contact to the most ventral in 15 incremental steps. Results: The center of the electric field location had a significant effect on both the P3 and P10 amplitude in all hemispheres where a peak was detected (P3, detected in 4 of 5 hemispheres, p < 0.0001; P10, detected in 5 of 5 hemispheres, p < 0.0001). Post-hoc analysis indicated furthermore that MICC technology can significantly refine the resolution of steering. Conclusion: Using MICC to incrementally move the center of the electric field to locations between adjacent DBS-contacts resulted in significantly different neurophysiological responses that may allow further precision of the programming of individual patients.